Comparison of copper covered and copper core sheath yarn for the fabrication of textile antenna / N. I. Zaidi ...[et al.] - Zaidi, N. I.; Ali, M. T.; Rahman, N. H. A.; Amin Nordin, M. S.; Sharatol Ahmad Shah, A. A.; Yahya, M. F. (UiTM Press, 2018)
This paper presents the comparison between copper covered and copper core sheath yarn performance for the development of conductive fabric antenna. Conductive fabric is a fabric that are able to conduct electromagnetic. This kind of fabric is crucial in the development of textile antenna for wearable application. Thus, the types of yarns to be used are important in order to develop conductive fabric antenna. Two designs of yarn are investigated, which are copper covered yarn and copper core sheath yarn. Antenna prototypes fabricated by using both yarns are developed and measured to validate the performance of the antenna. The antennas are fabricated on conductive fabrics, which are made from copper covered and copper core sheath yarn. The relation between different types of conductive yarns is studied and the antenna performance is analyzed. The results show that the copper covered yarn is superior as compared to the copper core sheath yarn in terms of its return loss (S11) and radiation pattern performance. From the studies, copper covered yarn closely resembles PEC and hence the result of copper covered structure has good agreement with simulation.